Book Review - Ken Stevens (Flexible Learning Association of New Zealand, 2012)
Education and mind in the knowledge age. Encyclopedia of distance learning, vols.1-4. E-learning: Teaching and professional development with the Internet. Women and distance education: Challenges and opportunities.